CULTURE OF DIFFERENT COUNTRIES AND ITS ROLE IN GLOBAL UNDERSTANDING - Jabborova Elinoza (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Abstract: This article analyzes the concept of culture as a multifaceted social phenomenon and its impact on international communication. In the era of rapid globalization, cultural awareness has transitioned from a general interest to a professional necessity. By examining the cultural models of various nations—including the East-West dichotomy and the unique heritage of Uzbekistan—the paper highlights how understanding diversity can prevent social friction and foster global cooperation.